Assessment of the Shear Bond Strength of Composite Resin to Fresh Amalgam Using Different Adhesion Protocols: An In Vitro Study - Haider Hasan Jasim; Mohammed K Gholam; Biland MS Shukri (Wolters Kluwer Medknow Publications, 2022)
Introduction: This study was conducted to evaluate and compare the effect of using three adhesive systems on the shear bond strength between composite resin and fresh amalgam. Materials and Methods: Amalgam samples were assigned into three groups according to the adhesive systems being used prior to the composite resin application. Group A (n = 10): universal self-etch bonding system (Single Bond Universal Adhesive, 3M, Neuss, Germany) was applied and light cured. Group B (n = 10): universal self-etch bonding was applied and light cured, followed by a thin layer of nanohybrid flowable composite (Tetric N-Flow, Ivoclar Vivadent, Liechtenstein), then light cured. Group C (n = 10): self-adhesive dual-cure luting resin cement (Calibra Universal, Dentsply Sirona, Charlotte, NC) was applied in equal quantity for each sample over amalgam surface. Composite resin was then applied by plastic instrument in a single increment to the height of the hole (2 mm), then celluloid strip was placed and light cured. After thermocycling, a shear bond test was performed. Results: Resin luting cement interface showed the higher significant bond strength, followed by universal bonding agent − flowable composite interface. The universal bonding interface group yielded the lowest results. Conclusion: The application of self-adhesive dual-cure luting resin cement resulted in significant increase in bond strength between composite resin and fresh amalgam.